Potential therapeutic of saffron (Crocus sativus L.) in the metabolic syndrome - de Alencar Britto, Revilane Parente; Veiga, Rogério da Silva; Marcucci, Maria Cristina [UNESP] (My University, 2019)
Over the last three decades, the interest of the scientific community in investigating the use of saffron (Crocus sativus L.) as a potential therapeutic or preventive agent for a number of health conditions has increased. The purpose of this review is to examine the therapeutic role of saffron and its products in cardioprotection, atherosclerosis, dyslipidemia, systemic arterial hypertension (HAS), diabetes, insulin resistance and obesity. Most of the therapeutic properties of saffron are due to the presence of carotenoids (crocin, crocetin and safranal) playing an important antioxidant and anti-inflammatory role, suppressing pro-inflammatory cytokines and reactive oxygen species, reducing oxidative stress, peroxidation lipid metabolism, endothelial dysfunction, atherosclerosis, hypertension, dyslipidemia, insulin resistance and appetite. Further evidence is needed to investigate the benefits and molecular mechanisms of action, doses, and toxicity of saffron and its constituents in humans.
Potencial terapéutico del azafrán {Crocus sativus L.) en el síndrome metabólico
Potencial terapêutico do açafrão (Crocus sativus L.) na síndrome metabólica
Keywords: Anti-inflammatory; Antioxidants; Cardiovascular disease; Crocus sativus; Metabolic syndrome; Saffron